First-Principles Studies On The Electronic And Mechanical Properties Of Two-Dimensional (2D) Materials - Ng, Yi Sheng (2020)
Since the discovery of Graphene, two-dimensional (2D) material or monolayer has been attracting huge interest. By stacking two different monolayers on top of one another, we can obtain heterostructure, which has different physical properties compared with the individual monolayers. In this work, using the first-principles method within the Density Functional Theory (DFT) framework, we have discovered a new stable heterostructure by stacking monolayer Ge (Germanene) and monolayer SiGe (Siligene). The new heterostructure is stable as evidenced by the lack of negative frequency in the phonon dispersion, and exhibits metallic characteristic as indicated by the presence of electronic states at the Fermi level. Under more than 6% tensile strain or 4% compressive strain, the heterostructure starts to fracture mechanically with ultimate tensile strength of about 18 GPa. Besides, the metallic characteristic of the heterostructure shifts from metallic to semimetallic under 6% biaxial tensile strain. When oxygen atoms are adsorbed onto the surface of the heterostructure, a band gap of 0.24 eV is induced. The metallic heterostructure may be applicable for future development of nano scale battery anode or IC interconnects.